2008
DOI: 10.1002/clc.20405
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of the Ezetimibe and Simvastatin in Hypercholesterolemia Enhances Atherosclerosis Regression Trial: A Return to First Principles

Abstract: To outward appearances, the publication of the Ezetimibe and Simvastatin in Hypercholesterolemia Enhances Atherosclerosis Regression (ENHANCE) trial has led to a monolithic backlash against the use of ezetimibe by cardiologists for the treatment of hyperlipidemia. Rather than be swayed by popular opinion, we should each put the results of ENHANCE into context and ask the questions: should I put my trust in an imaging surrogate or in low-density lipoprotein (LDL) cholesterol (LDL-C), and how do the safety and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Moreover, >80% of patients had previously received statins, which is likely to have affected how CIMT responded to further therapy. [12] In contrast, a 1-year trial in 90 high-risk coronary Mexican patients with thickened carotid walls found that dual ezetimibe plus statin therapy had beneficial effects on LDL-C levels that led to significant reductions in CIMT. [34] Patients were allocated to three groups that initially received ezetimibe 10 mg plus simvastatin 20 mg, pravastatin 40 mg, or simvastatin 40 mg; if lipid goals were not achieved, the regimen was increased to ezetimibe 10 mg plus simvastatin 40 mg (83% of patients in this group required this regimen), pravastatin 40 mg plus ezetimibe 10 mg (100%), and simvastatin 80 mg (55%), respectively.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, >80% of patients had previously received statins, which is likely to have affected how CIMT responded to further therapy. [12] In contrast, a 1-year trial in 90 high-risk coronary Mexican patients with thickened carotid walls found that dual ezetimibe plus statin therapy had beneficial effects on LDL-C levels that led to significant reductions in CIMT. [34] Patients were allocated to three groups that initially received ezetimibe 10 mg plus simvastatin 20 mg, pravastatin 40 mg, or simvastatin 40 mg; if lipid goals were not achieved, the regimen was increased to ezetimibe 10 mg plus simvastatin 40 mg (83% of patients in this group required this regimen), pravastatin 40 mg plus ezetimibe 10 mg (100%), and simvastatin 80 mg (55%), respectively.…”
mentioning
confidence: 92%
“…[25][26][27] A meta-analysis of 27 pooled clinical trials in hypercholesterolemic patients found improvements in lipid parameters (LDL-C, total cholesterol, HDL-C, non-HDL-C, triglycerides, and apolipoprotein B) were significantly greater with ezetimibe simvastatin than with a statin alone. [25] For example, in a 24-week, forced-titration trial (n = 787), ezetimibe simvastatin (10 mg 10 mg, 10 mg 20 mg, 10 mg 40 mg, or 10 mg 80 mg) was significantly more effective than monotherapy with corresponding atorvastatin (10, 20, 40, or 80 mg) in reducing plasma LDL-C levels and improving most other lipid parameters from baseline at the 6-week primary timepoint, as well at all secondary assessment points (12,18, and 24 weeks). [26] In 618 hypercholesterolemic patients who had previously received statin monotherapy in a 6-week trial, a switch to ezetimibe simvastatin 10 mg 20 mg was significantly more effective than a Table I.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, the publication of the ENHANCE trial has led to a monolithic backlash against the use of ezetimibe by cardiologists for the treatment of hyperlipidemia 12 . In fact, as the ENHANCE (Effect of Combination Ezetimibe and High-Dose Simvastatin vs. Simvastatin alone on the Atherosclerotic Process in Patients with Heterozygous Familial Hypercholesterolemia) study" clearly shows, treatment with ezetimibe plus statin does not have an increased effect on morbidity and mortality compared to statin treatment alone.…”
mentioning
confidence: 99%